Countryside Survey: National "Soil Change" 1978–2007 for Topsoils in Great Britain—Acidity, Carbon, and Total Nitrogen Status. Issue 2 (2nd May 2013) - Reynolds, B.; Chamberlain, P.M.; Poskitt, J.; Woods, C.; Scott, W.A.; Rowe, E.C.; Robinson, D.A.; Frogbrook, Z.L.; Keith, A.M.; Henrys, P.A.; Black, H.I.J.; Emmett, B.A.
Abstract : Understanding "soil change" at the national scale, in addition to soil status, is a key challenge for national scale soil monitoring programs and is essential if more sustainable use of this finite resource is to be achieved. We present results from the first national scale survey of soil change to be reported three times within Europe and perhaps globally, covering a 30‐yr time span. Countryside Survey is an integrated national monitoring program that makes measurements of vegetation; topsoil physical, chemical, and biological characteristics (0–15 cm); water quality; and land use across Great Britain (GB), thus recognizing their interdependence. Here we report on change in fundamental soil chemical characteristics. Soil pH and loss on ignition (LOI) were measured in 1978, 1998, and 2007 and soil total nitrogen (total N) concentration and C/N ratio in 1998 and 2007. Bulk density was measured in 2007. Mean soil pH increased significantly in less acidic soils from 1978 through 1998 to 2007. Mean pH increased significantly in more acidic, organic‐rich soils from 1978 to 1998 but not between 1998 and 2007, indicating spatial trends in both sulfur deposition reductions and soil sensitivity. There was a small increase (8%) in GB topsoil C concentration (calculated from LOI) between 1978 and 1998, a small decrease (6.5%) between 1998 and 2007, and no significant overall change between 1978 and 2007. The unresolved difference between these results and those from the National Soil Inventory of England and Wales that reported wide‐scale large decreases in soil C concentrations in 2005 are discussed. There were unexpected small but significant decreases in total N concentration in many broad habitats despite continuing atmospheric nitrogen deposition. In seminatural and woodland habitats, this was accompanied by an increase in the C to N ratio, indicating one possible explanation is dilution of the nitrogen signal due to high C/N litter inputs resulting from increased primary productivity as reported elsewhere due to a range of global drivers such as increased CO2, N, and temperature. In arable systems, comparable rates of loss of C and N suggest erosion losses or deep plowing are reducing soil condition. The results are discussed in relation to the influences on soil processes of key drivers of environmental change and the importance of considering habitat‐specific trends.